2022
DOI: 10.1530/ec-21-0282
|View full text |Cite
|
Sign up to set email alerts
|

100 YEARS OF VITAMIN D: Global differences in vitamin D status and dietary intake: a review of the data

Abstract: Background: Internationally, concern has been repeatedly raised about the little notable progress in the collection, analysis and use of population micronutrient status and deficiency data globally. The need for representative status and intake data for vitamin D has been highlighted as a research priority for well over a decade. Aim and methods: A narrative review which aims to provide a summary and assessment of vitamin D nutritional status data globally. It divides the World into the Food and Agri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
72
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 69 publications
1
72
0
4
Order By: Relevance
“…Epidemiological studies have documented a high prevalence of vitamin D deficiency worldwide [ 37 ]. Data from Europe showed that 25(OH)D concentrations below 20 ng/mL (50 nmol/L) and below 12 ng/mL (30 nmol/L) are observed in 40.4% and 13.0% of the general population, respectively [ 9 ].…”
Section: Consensus Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies have documented a high prevalence of vitamin D deficiency worldwide [ 37 ]. Data from Europe showed that 25(OH)D concentrations below 20 ng/mL (50 nmol/L) and below 12 ng/mL (30 nmol/L) are observed in 40.4% and 13.0% of the general population, respectively [ 9 ].…”
Section: Consensus Recommendationsmentioning
confidence: 99%
“…Therefore, we recommend a vitamin D supplement dose of at least 800 IU per day when targeting a sufficient vitamin D status, i.e., a 25(OH)D concentration of at least 20 ng/mL (50 nmol/L). We can, of course, improve and maintain vitamin D status by consuming natural or fortified food sources, but vitamin D intake by diet is usually in the range of about 100 to 200 IU per day in the general population [ 37 , 56 ].…”
Section: Consensus Recommendationsmentioning
confidence: 99%
“…Therefore, a diet with varying amounts of these food components would supply up to 15 μg of vitamin D equivalents per day. Dietary surveys of populations from around the world indicate, however, that the typical range of vitamin D daily intakes from unfortified food is from 0 to 5 μg/d ( 9 ) . It would follow that this would have been the range of daily intakes of vitamin D in human history before the discovery of this hormone precursor.…”
mentioning
confidence: 99%
“…Vitamin D2 (ergocalciferol, calcidiol) was isolated from a mixture of UV-irradiated ergosterol by Askew et al in 1928 ( 8 ). Windaus and colleagues eventually characterized 7-dehydrocholesterol and vitamin D3 as the natural vitamin D formed in the skin by UV-B irradiation of its precursor 7-dehydrocholesterol between 1935 and 1937 ( 9 , 10 ). The sterol expert Windaus had already been decorated by the Nobel committee for his research on the composition of sterols and their connection to vitamins in 1928.…”
mentioning
confidence: 99%
“…Controversies still exist regarding vitamin D requirements in normal health and disease under the epidemiological, preventive and health economics aspects related to different endpoints, biomarkers or surrogate outcome parameters. Global differences in vitamin D status and dietary intake have been identified, and remain extremely challenging in both developed and developing countries as reviewed by Cashman ( 12 ). Webb and coworkers evaluated available data for dose–response relationships for changes in 25OHD serum concentrations on whole-body exposure of the human fur-less skin to repeated sub-erythemal doses of UV radiation, revealing large interpersonal variations in response to UV exposure with skin type as a determinant of response to UV radiation ( 13 ), which makes the optimum sunlight exposure level for maximum vitamin D effects difficult to quantify.…”
mentioning
confidence: 99%